Halide segregation in mixed-halide perovskites: influence of a-site cations - Knight, AJ; Borchert, J; Oliver, RDJ; Patel, JB; Radaelli, PG; Snaith, HJ; Johnston, MB; Herz, LM (American Chemical Society, 2021)
Mixed-halide perovskites offer bandgap tunability essential for multijunction solar cells; however, a detrimental halide segregation under light is often observed. Here we combine simultaneous in situ photoluminescence and X-ray diffraction measurements to demonstrate clear differences in compositional and optoelectronic changes associated with halide segregation in MAPb(Br0.5I0.5)3 and FA0.83Cs0.17Pb(Br0.4I0.6)3 films. We report evidence for low-barrier ionic pathways in MAPb(Br0.5I0.5)3, which allow for the rearrangement of halide ions in localized volumes of perovskite without significant compositional changes to the bulk material. In contrast, FA0.83Cs0.17Pb(Br0.4I0.6)3 lacks such low-barrier ionic pathways and is, consequently, more stable against halide segregation. However, under prolonged illumination, it exhibits a considerable ionic rearrangement throughout the bulk material, which may be triggered by an initial demixing of A-site cations, altering the composition of the bulk perovskite and reducing its stability against halide segregation. Our work elucidates links between composition, ionic pathways, and halide segregation, and it facilitates the future engineering of phase-stable mixed-halide perovskites.